2004
DOI: 10.1142/s0192415x04002430
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Aqueous Extracts of "Betel Quid" and Its Constituents on Testosterone Production by Dispersed Mouse Interstitial Cells

Abstract: Betel quid (BQ) is a favorite chewing item among many communities in different parts of Asia where it is popular by different names. BQ is a unique combination of nut or fruit from the Areca catechu Linn. (AN) tree, leaf from the Piper betle Linn. (BL) vine, slaked lime, paste of bark from the Acacia catechu tree and other spices. AN has been used successfully in various traditional medicines by different civilizations over several ages. Initially condemned by the medical communities for its health hazards, id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…The elevation of testosterone level in this study may be mediated by serotoninergic action of serotoninergic agents to enhance testosterone synthesis (Yang et al, 2004). P. macrocarpa aqueous extract possesses significant sexual function enhancing activity as observed in libido behavior tests.…”
Section: Discussionmentioning
confidence: 79%
“…The elevation of testosterone level in this study may be mediated by serotoninergic action of serotoninergic agents to enhance testosterone synthesis (Yang et al, 2004). P. macrocarpa aqueous extract possesses significant sexual function enhancing activity as observed in libido behavior tests.…”
Section: Discussionmentioning
confidence: 79%
“…BTB provoked a rapid, profound increase in serum testosterone level again indicating its aphrodisiac credentials. The elevation of testosterone evident in this study may be mediated by serotoninergic action of BTB as serotoninergic agents are reported to enhance testosterone synthesis (Yang et al, 2004) or by preventing its metabolic degradation since flavones present in BTB (Modder and Amarakoon, 2002) are well-known aromatase-enzyme inhibitors (Anonymous, 2007).…”
Section: Discussionmentioning
confidence: 83%
“…Another study on the effects of aqueous extracts of "betel quid" (a combination of nut or fruit from Areca catechu, leaf from the Piper betel and paste of bark from Acacia catechu) and its constituents on testosterone production by dispersed mouse interstitial cells, found that lower doses of the extract arecoline, alone or in combination with 10 ng/ml ovine luteinising hormone significantly stimulated testosterone production over the basal level. However, when co-cultured with cAMP it became inhibitory (Yang et al, 2004).…”
Section: Discussionmentioning
confidence: 98%